Comparative Energy Analysis of a Load Sensing System and a Zonal Hydraulics for a 9-Tonne Excavator - Paolo Casoli; Fabio Scolari; Tatiana Minav; Massimo Rundo (Actuators, 2020)
With the rising demand for energy efficiency, displacement-controlled or so-called pump-controlled systems have become an attractive research topic for applications in construction machinery and other off-road vehicles. Pump-controlled systems can be implemented with electro-hydrostatic actuators as electro-hydraulic zones, which are located next to the end actuator as a replacement for the traditional valve-controlled hydraulic actuation systems. In this paper a 9-tonne class excavator is utilized as a study case. A mathematical model of the conventional machine, validated with tests carried out on both the excavator and the single hydraulic components, was previously developed within the Simcenter AMESim© environment. This mathematical model was modified with electric components for simulating a zonal hydraulics excavator and compared with a conventional load sensing (LS) machine. The energy efficiencies of both the LS circuit and the new solution were evaluated for typical duty cycles, pointing out the obtainable energy efficiency improvements, which were mainly due to the absence of the directional valves and pressure compensators. The results also point out the effect of the pipe losses when the circuit layout requires the pipe for connecting the pump with the actuator; moreover, the effect of a diesel engine downsizing on the energy saving was evaluated.